MANAGER TRAINING AND ITS INFLUENCE ON THE INCLUSION OF ICT IN PEDAGOGICAL PRACTICE - Luís Bender, André; Carla Beserra da Fonseca, Elizangela; Aureliano Santos de Araújo, Helen; Evangelista Da Silva, José; Luiz Da Silva Liria, João; Adriano Silva, Kleyton; Rodrigues da Silva Ueda, Larissa; Fagundes Goulart, Sheila; Guimarães Santos, Saulo; Maria de Melo Silva, Vaneska (Revista Gênero e Interdisciplinaridade, 2024)
School management is currently understood from the democratic and participatory principle, resulting in a more complex perception of the school manager’s participation in the success of the students’ learning process. In this sense, the perception of the concept of school manager has become broader, involving all aspects that directly or indirectly influence the quality of education in a given school institution. In this context, this article seeks to investigate how the continued training of school managers influences the quality of management performance and, consequently, the development of pedagogical planning that cooperates with the insertion of pedagogical practices based on the use of ICT and the adoption of a methodology from an innovative perspective.